Barriers to prevention in oral health care for english NHS dental patients: a qualitative study of views from key stakeholders - Heather Leggett; Karen Vinall-Collier; Julia Csikar; Gail Veronica Ann Douglas (BMC, 2023)
Abstract Background Despite significant progress in the control of oral diseases since the discovery of fluoride in the 1940s, dental caries and periodontal diseases continue to affect a significant proportion of the population, particularly socially disadvantaged and lower socioeconomic groups. The National Health Service in England provides preventive advice and treatments as part of an oral health assessment, and evidence-based guidance recommends the use of fissure sealants and topical fluorides in addition to dietary and oral hygiene advice. Although oral health promotion and education have become expected parts of dental care, the need for restorative treatments remains relatively high. We aimed to explore how barriers to preventive advice and treatment for NHS patients may be hindering the provision of prevention in oral health to patients from the perspectives of multiple key stakeholders. Methods Semi-structured interviews and focus groups were undertaken between March 2016-February 2017 with four groups of stakeholders: dentists, insurers, policy makers and patient participants. The interviews were analysed using deductive, reflexive thematic analysis. Results Thirty-two stakeholders participated: 6 dentists, 5 insurers, 10 policy makers, and 11 patient participants. Four themes were developed: Perspectives on the clarity of oral health messaging and patient's knowledge, The variability of prioritising prevention, Influences of the dentist-patient relationship on effective communication and Motivation to enact positive oral health behaviours. Conclusions The findings from this research indicate that patients' knowledge of and priority placed on prevention is variable. Participants believed that more targeted education could be valuable in enhancing these. A patient's relationship with their dentist could also influence their level of knowledge through the information shared with them, their receptivity to the preventive messages and the value they place on it. However, even with knowledge, prioritising prevention and a good patient-dentist relationship, without motivation to engage in preventive behaviour the impact of these is reduced. Our findings are discussed in relation to the COM-B model of behaviour change.